Study On The Effect Of Nitrite And Free Nitrous Acid On Cultivation Of Microalgae - Chan, Jyh Loong (Universiti Sains Malaysia, 2021)
Chlorella vulgaris was widely used as potential nutrients elimination microalgae in wastewater treatment plant due to its high removal efficiency of total nitrogen (TN) and total phosphorous (TP). The aim of this study was to study the effect of nitrite addition on microalgae cultivation by introduce 0 mg/L, 50 mg/L, and 100 mg/L of nitrite into batch reactors respectively, to investigate the effect of free nitrous acid (FNA) on microalgae cultivation by controlling microalgae cultivation condition in pH 4, 6, and 8 with addition 50 mg/L of nitrite into batch reactors respectively, and to evaluate the influence of FNA concentration on the extracellular polymeric substances (EPS) secretion from microalgae by conducting EPS extraction as well as proteins and polysaccharides analysis. The results show that 50 mg/L of nitrite introduced into microalgae cultivation had highest growth rate in the result of oxygen inhibition had been eliminated, while 100 mg/L of nitrite introduced into microalgae cultivation had lowest growth rate because of high FNA concentration presented. Moreover, microalgae cultivation with addition 50 mg/L of nitrite and pH 4 culturing condition show the lowest growth rate, and the growth rate for microalgae cultivated at pH 8 had slightly higher than microalgae cultivated at pH 6. From the aspects of proteins and polysaccharides released in EPS, the peak points for protein (PN) concentration released with condition of pH 4, 6, 8 were 156.06 ug/mL (at first day), 171.35 ug/mL (at seventh day), and 173.71 ug/mL (at ninth day), while polysaccharide (PS) released with pH 4 was up to 91.02 ug/mL at third day and reduced to 13.43 ug/mL at seventh day which almost similar trend with others cultivation systems. In overall, microalgae cultivation with addition 50 mg/L of N and pH culturing condition more than 6 could enhance the microalgae cultivation.